Mapping the movement for climate change and health in England: a descriptive review and theory of change analysis. (November 2021) - Issa, R; Baker, C; Spooner, R; Abrams, R; Gopfert, A; Evans, M; Aitchison, G
Aims: There are a growing number of organisations working to address the connections between climate change and health. This article introduces the concept of 'theories of change' – the methodology by which organisations or movements hope to bring about social change – and applies it to the current climate change and health movement in England. Through movement mapping, the article describes and offers reflections on the climate change and health ecosystems in England. Methods: Organisations working on climate change and health in England were identified and publicly available information was collated to map movement characteristics, target stakeholders and methodologies deployed, using an inductive, iterative approach. Results: A total of 98 organisations working on health and climate change (and/or sustainability) were initially identified, of which 70 met the inclusion criteria. Most organisations target two or more stakeholders, with healthcare workers, management structures, and government being most commonly cited. Methodological approaches identified include Formal education programmes; Awareness-raising; Purchasing-procurement power; Advocacy; Financial; Media-messaging; Networking; Knowledge generation; and Policy making, of which education, awareness-raising, and advocacy are most commonly used. Conclusion: There is a tendency for climate change and health organisations in England to focus on individual level and sectoral change over system change. More could be made of the potential for the healthcare professions' voice and messaging for the wider climate movement. Given the rapid boom of climate change and health organisations in recent years, a mind-set shift that recognises different players as part of a cohesive ecosystem with better coordination and collaboration may reduce unnecessary work, and facilitate more cohesive outcomes.